Comparison of antimicrobial efficacy of chlorhexidine and combination mouth rinse in reducing the Mutans streptococcus count in plaque - Laxmi S Lakade; Preetam Shah; Dayanand Shirol (Wolters Kluwer Medknow Publications, 2014)
Background: The removal of plaque is utmost important to control dental caries. But in children, factors like lack of dexterity, individual motivation and monitoring limit the effectiveness of tooth brushing. This necessitates the use of chemotherapeutic agents for control of plaque. Aims: To compare the antimicrobial efficacy of 0.2% chlorhexidine mouth rinse and mouth rinse containing 0.03% triclosan, 0.05% sodium fluoride, and 5% xylitol in reducing the Mutans streptococcus count in plaque. Materials and Methods: Thirty healthy children aged 8-10 years with dmft (decay component) of three or four were selected. They were divided randomly into two groups: The control or chlorhexidine group and the study group or combination mouth rinse. Both the groups practiced rinsing with respective mouth wash for 1 min for 15 d twice a day. The plaque samples were collected and after incubation Mutans streptococcus count was estimated on the strips from the Dentocult SM kit and evaluated using manufacture's chart. Statistical Analysis Used: Wilcoxon matched pairs signed ranks test and Mann-Whitney U test were used to analyze the findings. Results: Statistically significant reduction in the Mutans streptococci count in the plaque was seen in the control and study group from baseline level. But when both the groups were compared, the antimicrobial effect of chlorhexidine was more.